Elderly abuse: Suffering in silence - who is listening? Some concern for social work practices - Singh, Avtar; Duggal, Akshi; Singh, Ravinder; K. Talwar, Upmesh (International Journal of Health, 2015)
Paper highlights basic concepts of elder abuses and raises relevant issues concerning problems of elderly, which must be listened with utmost care. None of us claim convincingly that what is an extent of older personâ€™s problems and what is the appropriate solution. It is only possible through a caring unit of society, the family, if restructured on the values and reframing the sensitivity among kins n kieth. Then elderly people may get a meaningful relationship among the family of genitor and extended family of procreator â€“ younger children and their families. Otherwise their suffering, though how difficult or simple may, would continue as such, despite best economical resources, plans and programmes existing for them. Legal provisions to do exist to safeguard elderly people in family situations, butÂ they are neither aware nor their progeny for caring them in extended families. Do we hear them or spend quality time as married sons or daughters, daughter in laws? Do our children spend time with grandfather? Or do we not leave them to alone with their suffering in silence? Overall in last, we do not have enough time to listen their problems-being alone, emotional disturbances, etc., and they remain to suffer in silences.